TEACHER/LEARNER RATIO ON EFFECTIVE CURRICULUM IMPLEMENTATION IN PUBLIC EARLY CHILDHOOD DEVELOPMENT AND EDUCATION CENTRES IN MUHORONI SUB-COUNTY, KENYA - Celestine Mary Atieno (International Journal of Research Science and Management, 2017)
Early Childhood Development and Education (ECDE) programme for years has not been part of the mainstream education services, with the programme provision left to various stakeholders in a totally uncoordinated manner. However, in the recent past, the government through the Ministry of Education has introduced an ECDE curriculum and is making an effort to see that it is fully implemented. The objective of the study wasto determine how teacher/learner ratio affects curriculum implementation in public ECDE centres in Muhoroni Sub-County. The study adopted descriptive survey design. Questionnaires and Observation Checklists were used to collect data. The researcherused descriptive methods to analyse data. Sample for the study was 30 ECDE centres which included 30 head teachers of the primary schools in which the ECDE centres were attached and all the ECDE teachers in the sampled centres. Cluster sampling and simple random sampling techniques were used for the study. Data analysis was undertaken primarily in terms of percentages and, to a lesser extent, through descriptive analysis. Based on research findings, the study concluded that there were low teacher learner ratios. Finally, the study recommended that more ECDE teachers be employed to meet the needs of rising enrolment in public ECDE centres.